The Labor Law and the Sharing Economy - Lizama Portal, Luis (2020)
In this article the authors develop the issue about if it is generated a right of control between employer and employee and thereby an employment relationship on Sharing Economy. For this purpose, the authors analyze diverse concepts from Labor Law and Sharing Economy, to finally apply the test that they consider to be appropriate to assess the existence of an employment relationship on these markets. The importance of the article is clear, since both nationally and internationally is currently being discussed if in this economic phenomenon an employment relationship is generated.